Beam and target parameters measurement system on helium ions linear accelerator - Anokhin, R.A.; Dubnyuk, S.N.; Dyachenko, A.F.; Kobets, A.P.; Manuilenko, O.V.; Pavlii, K.V.; Shevchenko, A.S.; Soshenko, V.A.; Tishkin, S.S.; Zabotin, A.V.; Zajtsev, B.V.; Zhuravlyov, A.V. (Вопросы атомной науки и техники, 2018)
A system for measuring beam and target parameters on helium ions linear accelerator is presented. The measurement system consists of sensors set, signal converters and computer with codes for processing experimental data. The measurement system is designed for recording, visualizing, storing and processing data directly when samples are irradiated with helium ions with energies of 0.12…4 MeV. The sample temperature, the ion beam current and its shape, the sample tilt angle to the beam axis, the irradiation dose, the ionization, damage and helium range profiles are measured/calculated.